Van Allen Probes Observations of Symmetric Stormtime Compressional ULF Waves. Issue 2 (12th February 2022) - Takahashi, Kazue; Crabtree, Chris; Ukhorskiy, A. Y.; Boyd, Alexander; Denton, Richard E.; Turner, Drew; Gkioulidou, Matina; Vellante, Massimo; Spence, Harlan E.
Abstract: Previous spacecraft studies showed that stormtime poloidal ultralow‐frequency (ULF) waves in the ring current region have an antisymmetric (second harmonic) mode structure about the magnetic equator. This paper reports Van Allen Probes observations of symmetric ULF waves in the postnoon sector during a moderate geomagnetic storm. The mode structure is determined from the presence of purely compressional magnetic field oscillations at the equator accompanied by strong transverse electric field perturbations. Antisymmetric waves were also detected but only very late in the recovery phase. The symmetric waves were detected outside the plasmasphere at L  = 3.0–5.5 and had peak power at 4–10 mHz, lower than the frequency of the local fundamental toroidal standing Alfvén wave. During the wave events, the flux of protons was enhanced at energies below ∼5 keV, which appears to be a prerequisite for the waves. The protons may provide free energies to waves through drift resonance instability or drift compressional instability, which occur in the presence of radial gradients of plasma parameters. Plain Language Summary: During geomagnetic storms, the intensity of the flux of ions is elevated in the magnetosphere including the region inward of geostationary orbits. The ions are capable of exciting a variety of plasma waves including ultralow‐frequency (ULF) waves in the frequency range 1–20 mHz. Stormtime ULF waves with a strong perturbation of the magnetic field magnitude are commonly detected at geostationary orbit and are known to commonly have a standing wave structure along the background magnetic field that is antisymmetric about the magnetic equator. Observations made by the Van Allen Probes provide new evidence that symmetric waves are also excited inward of geostationary orbits. The waves are observed in association with enhancement of the flux of protons at energies below 5 keV. The waves may be excited by the spatial gradient of parameters associated with the ions. Key Points: Symmetric compressional ULF (4–10 mHz) waves were excited at L  = 3.0–5.5 during a geomagnetic storm The waves were associated with enhancement of the flux of protons at energy <5 keV Drift compressional instability is a possible wave generation mechanism